Optimal Damper Placement Using Combined Fitness Function - Bogdanovic, Aleksandra; Rakicevic, Zoran (Frontiers in Built Environment, 2019)
Passive control of structures represents practical concept and qualitative change of the design and construction of new seismically resistant structures and strengthening of existing ones. The best distribution obtained by the minimization or maximization of the defined structural responses is achieved by optimal placement of the different types of control devices in structures. In this paper will be presented the procedure for optimal placement of viscous damping device (PDD – Prestressed Damping Device-PDD) space distributed in structure for controlling the structural response due to seismic excitation. For the purpose of determination of the optimal location of the PDDs, 3D five story steel frame structure has been designed according to the Eurocode 3 and Eurocode 8 requirements. Nine previously defined initial configurations have been used as a starting point in the process of optimization. The desired performance has been defined using the derivate fitness function combined from the inter-story drift and energy dissipated ratio by PDDs vs input energy in the structure in two directions x and y. The value of the fitness function has been used to rank and quantify the optimum of the particular solution among all other solutions in the optimization process. Numerous nonlinear analyses have been conducted and a lot of analytical results have been collected in order to confirm the validity and the application of the presented procedure including the fitness function in any steel structure.